Устройство для охлаждения элементов микроэлектронной аппаратуры - Ashcheulov, A. A.; Okhrem, V. G.; Okhrem, Ye. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
This paper describes the physical principles of operation and the design of a galvanothermomagnetic cooler operating at temperatures at or below the boiling point of liquid nitrogen. The operating principle of the described device is the Thomson effect, which occurs in bismuth due to a change in the magnitude and sign of the longitudinal thermo-EMF upon inversion of the transverse magnetic field induction. The cooler can achieve a temperature reduction of 30 K below the boiling point of liquid nitrogen and can be used to cool microelectronic components.